Analysis of the stress distribution of North Anatolian Fault Zone for the part between Amasya-Tokat cities - Fikret Doğru; Oya Pamukçu; Ufuk Aydın; Ayça Çırmık (Bulletin of the Mineral Research and Exploration, 2022)
Tectonic forces formed in the continental crust, cause permanent changes in stress, compression and deformation. The amplitudes of earthquake waves vary with the stress/strain distribution in the crust. In this study, the change of stress/strain and regional absorption coefficient, which is effective in tectonic forces caused by elastic deformation energy accumulating in the brittle crust over time, was investigated. The study area is the middle part of the North Anatolian Fault Zone and the area formed by Ezinepazarı fault zone and Merzifon fault zone. In this area, Coulomb stress analysis was carried out by using the focal mechanism solution values of the earthquake that occurred in Yoldere - Erbaa, Tokat on October 9, 2015 (ML=5.1). In order to examine the deformation caused by this earthquake in and around the study area, Global Navigation Satellite System (GNSS) data were evaluated and the velocities of these stations were calculated using GNSS data of these stations for the years 2013-2014-2015-2016. Also, regional absorption coefficients were determined by using earthquake data. As a result, Coulomb stress analysis results, velocity values distribution obtained from GNSS data and absorption findings obtained from seismological  study were evaluated together.